Participant responsibility, researcher vulnerability and empirical ethics: a reply to Loughlin. Issue 3 (21st May 2013) - Duncan, Peter; Stephenson, Anne
Abstract In a recent issue of this journal, Michael Loughlin offers a critique of work we undertook that we described and discussed in the same issue, and which might be seen as forming part of the so‐called empirical turn in ethics. Here we respond to Loughlin's criticisms of our work. While he declares that generally, there is potential value in empirically informed ethics, we understand him to be concerned about our particular project on two counts. First, he is worried by the extent to which participants exercised responsibility within the work; and second, he is concerned about the degree to which we, as researchers, were prepared rigorously to examine and question participant assertions and assumptions. We argue that Loughlin's worries are based on a relatively limited view of the context in which empirically informed ethics related to health care takes place. A more complex understanding than he allows, of both the responsibility of participants and the vulnerability of researchers who are involved in projects of empirical ethics in this context, is required in order to recognize the ambiguities and difficulties faced by those involved in such projects.